Undian Berhadiah Giveaway dalam Akun Instagram @Krd.Shopgaming : Analisis Hukum Ekonomi Syariah - Nurbaet, Mufli; Fauzan, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Giveaways in online businesses are intended to attract buyers and are used as a marketing strategy. However, giveaways are burdened with several conditions that followers must meet, some even have to pay in advance. This study aims to examine the giveaway on the Instagram account @krd.shopgaming, which is analyzed using Islamic Economic Law. The research method uses a qualitative approach with data sources being followers on the Instagram account @krd.shopgaming. Data collection techniques use observation, interviews, and document studies. The analysis technique uses an interactive model. The results of the study show that the giveaway prize draw on the online shop organized by the Instagram account @krd.shopgaming, based on previously determined conditions, is valid according to Islamic economic law. This validity is because the participants, both those who receive and those who do not receive prizes, agree without coercion, so that there is no loss for the participants. This study contributes to the development of Islamic economic law in solving contemporary problems today.